THE TECHNICAL-SPECIALIZED TRANSLATOR, AN AGENT CAUGHT IN-BETWEEN FIELDS: A NARRATIVE FROM A PRACTICAL APPROACH - Udinal, Fernanda Teresinha [UNESP] (Univ Federal Santa Catarina, Nucleo Traducao, 2023)
Translation goes through other fields and goes beyond the textual level. The activity of translating brings aspects that permeate cognitive, social, and cultural aspects. In this article, we apply sociology to Translation Studies by adopting a Bourdieu-based approach to show the structure and the interactions among social agents in the field of translation and in the fields where technical-specialized translators find themselves when developing a translation project. From a practical experience of a professional translator with the translation of a web-based educational platform into Portuguese, we show how important it is for translators to be aware of the structure, norms, and interactions in that specific field so they can draw up their strategies and choices to succeed in their search for recognition and symbolic capital. First, we review key concepts of Bourdieu's theory of practice and then we advance in the discussion about the dynamics among the agents engaged in the translation project and language implications from a sociological perspective.
Keywords: Technical-specialized translation; Translation Studies; Bourdieu; Sociology in translation